2001
DOI: 10.1200/jco.2001.19.16.3596
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Waldenstrom’s Macroglobulinemia With Thalidomide

Abstract: Our data indicate that thalidomide has activity in WM but only low doses were tolerated in this elderly patient population. Confirmatory studies as well as studies that will combine thalidomide with chemotherapy or with rituximab may be relevant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 113 publications
(47 citation statements)
references
References 18 publications
1
43
0
2
Order By: Relevance
“…During recent years, combination therapies with rituximab have resulted in good overall response rates but low complete response rates [23,24]. Newer therapies, including thalidomide and bortezomib have shown encouraging results; however, they were introduced during the last calendar period of this study and may have only a marginal effect on survival in this study [25][26][27][28][29]. Studies evaluating the effect of autologous stem cell transplantation in LPL/WM have been promising with low toxicities and high response rates [5,[30][31][32][33][34].…”
Section: Discussionmentioning
confidence: 86%
“…During recent years, combination therapies with rituximab have resulted in good overall response rates but low complete response rates [23,24]. Newer therapies, including thalidomide and bortezomib have shown encouraging results; however, they were introduced during the last calendar period of this study and may have only a marginal effect on survival in this study [25][26][27][28][29]. Studies evaluating the effect of autologous stem cell transplantation in LPL/WM have been promising with low toxicities and high response rates [5,[30][31][32][33][34].…”
Section: Discussionmentioning
confidence: 86%
“…Thalidomide has been evaluated for the therapy of other plasma cell proliferative disorders like Waldenström's Macroglobulinemia (WM) [46] and Systemic amyloidosis [47] (Table 3). It has also been evaluated in the therapy of acute myelogenous leukemia (AML) [48] where the authors also observed a significant decrease in the microvessel densities in the responding patients treated with thalidomide, which was accompanied by declining plasma levels of bFGF.…”
Section: Multiple Myeloma and Other Hematological Malignanciesmentioning
confidence: 99%
“…Dimopoulos and colleagues [71] reported on 20 patients treated with thalidomide as a single agent at a median dose of 200 mg/day. Five of 20 patients achieved a 50% reduction in serum monoclonal IgM protein.…”
Section: Thalidomidementioning
confidence: 99%